A Comparative Study on Solubilities and Refractive Indices of Aqueous Solutions of Sodium and Calcium Salts of α-Amino Fatty Acids - Verma, R.P.; Kumar, Surendra (Asian Journal of Chemistry, 2010)
Solubilities and refractive indices of sodium and calcium salts of α-amino isovaleric, α-amino β-hydroxy butyric and α-amino isocaproic acids have been studied. Solubilities, apparent heat and entropy of solution suggest the existence of aggregates of salt above K.P. (323 K) in water. The C.M.C. has been determined by refractive index using Lorentz-Lorenz equation. The values of molar refraction of soap, [R]2, of calcium salts are found higher than sodium salts.